P90 Towards a protocol for the management of very severe chronic lung disease. (12th November 2015) - Hurley, M; Khetan, R; Bhatt, J
Abstract : Background: While corticosteroids appear effective in reducing respiratory support requirements of babies with very severe chronic lung disease of prematurity (CLD), controversy remains regarding the most appropriate route, timing, preparation and dosage. Using Delphi methodology, consensus was reached involving 4-weekly pulses of methylprednisolone for 3 days at 500 mg/m 2 in ventilator-dependent, or close to ventilation, babies in diffuse lung disease of childhood (Cunningham S., et al . Am J Respir Crit Care Med 189;2014:A4664). Use of hydroxychloroquine and azithromycin also reached consensus. Aims and objectives: To describe the features of those babies who received methylprednisolone, hydroxychloroquine and azithromycin ("consensus treatment") for severe CLD compared to those who did not in order to inform the drafting of a protocol. Methods: A prospective database detailing care of babies with severe CLD referred to the CLD service at Nottingham Children's Hospital Jan 2009–Dec 2014 was used. Results: 147 children were referred to the service; 4 babies received consensus treatment. Those receiving consensus treatment were ventilated for longer 39(sd 4.6) versus 8(sd 16.8) days (p < 0.001). Children receiving consensus treatment were significantly older at discharge 245(65) versus 95(45.5) days and were discharged with higher oxygen requirements (1.0(0.4) vs. 0.3(0.2) litres). Conclusions: Babies with very severe CLD were successfully treated with consensus treatment. A change in practice toward discharge at higher oxygen delivery rates in such babies was safe. Further experience will refine the objective criteria for considering consensus treatment and would inform the design of a future randomised controlled trial.